PERLINDUNGAN HUKUM DAN AKIBAT HUKUM ANAK DARI PERKAWINAN TIDAK TERCATAT (Studi di Pengadilan Agama Tulungagung) - Nawawie, A. Hasyim (Ahkam: Jurnal Hukum Islam, 2015)
Marriage which is not registered but conducted by some Muslims in Indonesia adopts the principles of fiqh which state that a marriage is valid if it meets the requirements of Islamic marriage. The status of children born from such kind of marriage gains the same recognition with a recorded marriage. However, in view of the state law, in the absence of his parentsâ marriage certificate, birth certificate of a childâs biological fatherâs name is not listed and only listed the name of the mother who gave birth. The child, then, cannot perform civil law relationship with her biological father. The child only has a civil relationship with his mother and his motherâs family. The legal protection for children of unregistered marriage is possible through Ithbat nikah (marriage determination), the determination of the origin of child who through the religious court. After doing ithbat marriage the child can be registered as a legitimate through the religious court decisions. The determination of the origin of the child come up with some consequences: the child becomes legal,the onset of the rights and obligations between parent and child and viceversa, the incidence of inherited inheritance between parent and child, orvice versa, the barrier Nasabiyah in marriage, girls are entitled to a marriage guardian of a male parent, the child is entitled to custody of her parents.Kata kunci: Perlindungan Hukum Anak, Perkawinan tidak Tercatat,Pengadilan Agama